Ossified pterygo-spinous ligament: incidence and clinico-anatomical relevance in the adult human skulls of North India - Yadav, Yogesh; Goswami, Preeti; Vellalacheruvu, Chakradhar (International Journal of Research in Medical Sciences, 2017)
Study of skulls has attracted the attention of anatomists since ages and sporadic attempts have been made to study skulls from time-to-time. Talking about the pterygoid processes of sphenoid bone, the irregular posterior border of lateral pterygoid plate usually presents, towards its upper part, a pterygo-spinous process, from which the pterygo-spinous ligament extends backwards and laterally to the spine of sphenoid. This ligament sometimes gets ossified as pterygo-spinous bar and a foramen is then formed named pterygo-spinous foramen, for the passage of muscular branches of mandibular nerve. The present study was undertaken to observe the incidence and status of pterygo-spinous bony bridge and foramen, its variations and clinical relevance in the adult human skulls of North India. For this purpose, 50 skulls were observed, pterygo-spinous bars were found to be present in 7 skulls, out of which completely ossified pterygo-spinous bony bridges were present in 2 skulls while 5 skulls had incompletely ossified pterygo-spinous ligaments. Such variations are of clinical significance for radiologists, neurologists, maxillo-facial & dental surgeons and anaesthetists, too.